The new theology and the old religion: being eight lectures, together with five sermons - Gore, Charles (E.P. Dutton, 1907)
Lectures: The new theology. The old religion. The immanence of God. The idea of sin. The meaning of Christ's divinity. Miracles. The atonement and the inspiration of Scripture. The new theology and the Church of England.--Sermons: The creed and common life. The permanent creed. The Christian idea of sin. Sacrifice, the genius of Christianity. The church and the poor.--Appendix: Report on the moral witness of the church on economic subjects.